Efficacy of Kisspeptin-54 to Trigger Oocyte Maturation in Women at High Risk of Ovarian Hyperstimulation Syndrome (OHSS) During In Vitro Fertilization (IVF) Therapy - Abbara, Ali; Jayasena, Channa N.; Christopoulos, Georgios; Narayanaswamy, Shakunthala; Izzi-Engbeaya, Chioma; Nijher, Gurjinder M. K.; Comninos, Alexander N.; Peters, Deborah; Buckley, Adam; Ratnasabapathy, Risheka; Prague, Julia K.; Salim, Rehan; et al. (The journal of clinical endocrinology and metabolism, 2015)
Context:In vitro fertilization (IVF) treatment is an effective therapy for infertility, but can result in the potentially life-threatening complication, ovarian hyperstimulation syndrome (OHSS).Objective:This study aimed to investigate whether kisspeptin-54 can be used to effectively and safely trigger oocyte maturation in women undergoing IVF treatment at high risk of developing OHSS.Setting and Design:This was a phase 2, multi-dose, open-label, randomized clinical trial of 60 women at high risk of developing OHSS carried out during 2013–2014 at Hammersmith Hospital IVF unit, London, United Kingdom.Intervention:Following a standard recombinant FSH/GnRH antagonist protocol, patients were randomly assigned to receive a single injection of kisspeptin-54 to trigger oocyte maturation using an adaptive design for dose allocation (3.2 nmol/kg, n = 5; 6.4 nmol/kg, n = 20; 9.6 nmol/kg, n = 15; 12.8 nmol/kg, n = 20). Oocytes were retrieved 36 h after kisspeptin-54 administration, assessed for maturation, and fertilized by intracytoplasmic sperm injection with subsequent transfer of one or two embryos. Women were routinely screened for the development of OHSS.Main Outcome Measure:Oocyte maturation was measured by oocyte yield (percentage of mature oocytes retrieved from follicles ≥ 14 mm on ultrasound). Secondary outcomes include rates of OHSS and pregnancy.Results:Oocyte maturation occurred in 95% of women. Highest oocyte yield (121%) was observed following 12.8 nmol/kg kisspeptin-54, which was +69% (confidence interval, −16–153%) greater than following 3.2 nmol/kg. At all doses of kisspeptin-54, biochemical pregnancy, clinical pregnancy, and live birth rates per transfer (n = 51) were 63, 53, and 45%, respectively. Highest pregnancy rates were observed following 9.6 nmol/kg kisspeptin-54 (85, 77, and 62%, respectively). No woman developed moderate, severe, or critical OHSS.Conclusion:Kisspeptin-54 is a promising approach to effectively and safely trigger oocyte maturation in women undergoing IVF treatment at high risk of developing OHSS.